1996
DOI: 10.1258/1357633961929402
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology in the Highlands of Scotland

Abstract: A pilot study of telemedicine consultations of 51 dermatology patients showed that the technology worked well, with the diagnosis being able to be made in most patients and over half of the patients being able to be dealt with through this medium only. It could therefore have a valuable screening role. However, many of the patients, in spite of the obvious advantage of an immediate consultant opinion, felt it would be more appropriately used as a review technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 0 publications
2
32
0
1
Order By: Relevance
“…Seven patients refused to participate. The reasons given included a dislike of machines (4), lack of time (2), and frustration with the skin problem (1). No obvious common characteristic explained their lack of participation.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven patients refused to participate. The reasons given included a dislike of machines (4), lack of time (2), and frustration with the skin problem (1). No obvious common characteristic explained their lack of participation.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…[1][2][3][4] The lack of influence of bandwidth on patient satisfaction suggests that the quality of transmission provided at 1 ⁄4 T1 bandwidth was sufficient for good physician and patient rapport. Age proved to be an independent predictor of patient acceptance; older patients were less inclined to embrace the new technology.…”
Section: Patient Provider and Nurse-escort Impressionsmentioning
confidence: 99%
“…Relatively few studies evaluated referring provider satisfaction in LI teledermatology. While there was some dissatisfaction associated with technical difficulties, most referring providers report being satisfied with the LI teledermatology (Gilmour et al, 1998;Jones et al, 1996). Similar to dermatologists who practice S&F teledermatology, dermatologists who practice LI teledermatology report being satisfied with practicing LI teledermatology.…”
Section: Satisfaction With Live Interactive Teledermatologymentioning
confidence: 93%
“…Over half of the patients could then be dealt with by the general practitioner immediately after consultation. 25 Common wisdom sees this type of service as a useful means of screening patients prior to being seen by specialists, especially if travel is involved. However, in this study the patients suggested that they preferred an initial face-to-face consultation with the specialist dermatologist, and that the teleconsultation would have been better used for subsequent review of their progress.…”
Section: Communication and Primary Carementioning
confidence: 99%